Insertion torque, flexural strength and surface alterations of stainless steel and titanium alloy orthodontic mini-implants: an in vitro study - Gustavo Lopes PULS; Guido Artemio MARAÑÓN-VÁSQUEZ; Christian Andrew Vargas RAMOS; Caio Luiz Bitencourt REIS; Andréa Cândido dos REIS; Maria Bernadete Sasso STUANI; Fábio Lourenço ROMANO; Mírian Aiko Nakane MATSUMOTO (Dental Press Editora, 2024)
ABSTRACT Objective: This study aimed to compare the insertion torque (IT), flexural strength (FS) and surface alterations between stainless steel (SS-MIs) and titanium alloy (Ti-MIs) orthodontic mini-implants. Methods: Twenty-four MIs (2 x 10 mm; SS-MIs, n = 12; Ti-MIs, n = 12) were inserted on artificial bone blocks of 20 lb/ft3 (20 PCF) and 40 lb/ft3 (40 PCF) density. The maximum IT was recorded using a digital torque meter. FS was evaluated at 2, 3 and 4 mm-deflection. Surface topography and chemical composition of MIs were assessed by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). General linear and mixed models were used to assess the effect of the MI type, bone density and deflection on the evaluated outcomes. Results: The IT of Ti-MIs was 1.1 Ncm greater than that obtained for the SS-MIs (p= 0.018). The IT for MIs inserted in 40 PCF test blocks was 5.4 Ncm greater than that for those inserted in 20 PCF test blocks (p < 0.001). SS-MIs inserted in higher density bone (40 PCF) had significantly higher flexural strength than the other groups, at 2 mm (98.7 ± 5.1 Ncm), 3 mm (112.0 ± 3.9 Ncm) and 4 mm (120.0 ± 3.4 Ncm) of deflection (p< 0.001). SEM evidenced fractures in the Ti-MIs. EDS revealed incorporation of 18% of C and 2.06% of O in the loaded SS-MIs, and 3.91% of C in the loaded Ti-MIs. Conclusions: Based on the findings of this in vitro study, it seems that SS-MIs offer sufficient stability and exhibit greater mechanical strength, compared to Ti-MIs when inserted into higher density bone.